FIQIH MUAMALAH IN VARIOUS ASPECTS - Luklu’ul Mutmainnah (Al-Qalam Institute, Probolinggo, East Java, Indonesia, 2023)
The term muamalah we often hear in everyday life and is usually associated with Islamic terms. Muamalah is an important thing that needs to be studied, especially economic actors among Muslims. The term muamalah is usually interpreted as a social relationship between humans. People's lives will be considered good when they can benefit others. In this case we need to learn what muamalah fiqh and the aspects in it so that we are not mistaken in carrying out economic activities that have Islamic status.